Formação continuada do professor de educação física em tecnologia assistiva visando a inclusão - Fiorini, Maria Luiza Salzani [UNESP] (2015)
The research aimed to plan, implement and evaluate a Continuing Education Program focused on physical education teachers with the objective of providing access to resources and strategies from the Assistive Technology for educational scholar of students with disabilities and students with autism. The theoretical and methodological approach was based on reflective and collaborative research. Participants were physical education teachers who taught classes for students with disabilities and students with autism in Elementary School at City Schools, first years. To reach the purpose, five studies were outlined. In the Preliminary study it was characterized target city for the research in relation to the enrollment of students with special educational needs in Elementary School at City Schools. In the Study 1, 17 teachers were divided into two groups, with the objective of identifying the difficulties when regarding inclusion, six meetings were had, three for each group. From these three meetings, in two data were collected through focus group, and in one meeting the feedback was done. From the analysis of the categorical content, eight categories of assigned difficulties emerged in regards to: 1) the formation; 2) the administrative-school issue; 3) the Student; 4) the diagnosis; 5) the Family; 6) the Pedagogical Resource; 7) the teaching strategy; 8) the Physical Education. In Study 2, two teachers were selected who had participated in a previous study, and in order to identify situations of difficulty and success to include students with disabilities and students with autism, recordings and observations of 12 classes of P11 and 16 classes of P2 were done. The recordings were categorized into themes. For P11 four themes were identified, namely: success situations and difficulties related to the strategy, the needs of students and the lack of purposeful action in relation to inclusion. For P2, seven themes were identified: the situations...